(3GQJjGM GdGcHGO HCQHGM abO GdChdGOs - (3CHh GdNjQ eMeO Hf YHO GdQMef Hf eMeO GdSNGhis; (3GdSNGhj , TeS GdOjf eMeO Hf YHO GdQMef Hf eMeO GdSNGhj, GdSNGhj,J (B902 (3g` s ((3YHO GdhgGH Hf eMeO Hf YeQ Gdajhei s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CJbf aYdg GdHOjY ai YHGOg hHYO adeG cGf GdehJ gh hcGf aQGb GdeMHhH ef CYXe GdeUGjH s
(3BNQgG (B:s
(3cGf eMchd jbhd (B: (3Gddge GfaYfG HGdYde hRjfG HGdMde hLedfG HGdJbhi hcQefG HGdYGajI BNQ GQJjGM GdCcHGO s
(3GdfSNI HgG MhGTs
(3GdhQbI GdChdi abW JMJhi Ydi LOGhds
(3GfJgi GdeDda ef JHjV GdcJGH SfI (B864s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs